2012
DOI: 10.1371/journal.pone.0049749
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of BamB from Pseudomonas aeruginosa and Functional Evaluation of Its Conserved Structural Features

Abstract: The assembly of β-barrel Outer Membrane Proteins (OMPs) in the outer membrane is essential for Gram-negative bacteria. The process requires the β-Barrel Assembly Machine (BAM), a multiprotein complex that, in E. coli, is composed of the OMP BamA and four lipoproteins BamB-E. Whereas BamA and BamD are essential, deletion of BamB, C or E produce membrane permeability defects. Here we present the high-resolution structure of BamB from Pseudomonas aeruginosa. This protein can complement the deletion of bamB in E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Based on analysis of its high-resolution structure, BamB has been proposed to interact directly with nascent OMPs (Gatsos et al, 2008; Heuck et al, 2011). However, experimental testing of those proposals has been negative (Jansen et al, 2012). The non-essential lipoprotein may instead have a role in modulating the conformations of the essential subunits BamA and BamD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on analysis of its high-resolution structure, BamB has been proposed to interact directly with nascent OMPs (Gatsos et al, 2008; Heuck et al, 2011). However, experimental testing of those proposals has been negative (Jansen et al, 2012). The non-essential lipoprotein may instead have a role in modulating the conformations of the essential subunits BamA and BamD.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of all the individual BAM subunits have been reported (Albrecht and Zeth, 2011; Endo et al, 2011; Heuck et al, 2011; Jansen et al, 2012; Kim and Paetzel, 2011; Knowles et al, 2011; Noinaj et al, 2011; Noinaj et al, 2013; Sandoval et al, 2011; Warner et al, 2011). BamA is a β-barrel OMP with an N-terminal periplasmic domain composed of five po lypeptide tr anslocation a ssociated (POTRA) motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a conformational cycle has been proposed for the BamA-assisted OMP folding and insertion that is modulated by mutation in some lipoprotein subunits of BAM (30). As BamA by itself has recently been reported to catalyze folding and insertion of substrate OMPs into liposomes in vitro (31), one important role of the BAM lipoproteins may be to modulate BamA conformation and increase the efficiency of the machinery (8). Therefore, understanding how the BAM lipoproteins interact with BamA is crucial to define their functional role.…”
Section: Discussionmentioning
confidence: 99%
“…High resolution structures of the individual BAM subunits have been reported (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Genetic and biochemical studies have shown that BamA interacts directly with BamB and BamD, whereas BamC and BamE are in contact with BamD (1,2,15,16).…”
mentioning
confidence: 99%
“…Subsequent studies showed that lateral opening of the barrel domain was required for function in BamA, strengthening an existing hypothesis that the barrel domain must open laterally in the membrane to allow insertion of the substrate OMPs into the OM (16, 18, 24). It has been proposed that BamB might serve as a scaffold, assisting in the handoff of nascent OMPs by SurA/Skp to BamA, while BamC, BamD, and BamE may serve support roles in regulating the function of BamA (14, 17, 25). The structures have offered clues to how each component may function within the complex; however, the lack of structural information regarding the fully assembled complex has hindered progress towards exploring the mechanism further.…”
mentioning
confidence: 99%